2022
DOI: 10.21203/rs.3.rs-2093332/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: GRP75 modulates endoplasmic reticulum-mitochondria coupling and accelerates Ca 2+ -dependent endothelial cells apoptosis in diabetic retinopathy

Abstract: Background Endoplasmic reticulum (ER) and mitochondrial dysfunction play fundamental roles in the pathogenesis of diabetic retinopathy (DR). The communication between the mitochondria and the ER is mediated by a functional subdomain referred to as the mitochondria-associated membrane (MAM). However, the mechanism underlying material exchange between the ER and mitochondria are poorly understood. This study aimed to explore the role of IP3R1-GRP75-VDAC1 axis in modulating Ca2+ homeostasis in RMECs. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…As a result of diabetes, many metabolic changes occur within the cell, leading to an increased level of oxidative stress, which may contribute to the regression of telomere length [45] . There was also an association between DR and increased oxidative stress and activation of proin ammatory signaling pathways [19,46] . As a result of chronic hyperglycemia induces a set of metabolic abnormalities that enhance ROS generation and ultimately lead to oxidative stress in the retina, resulting in retinal cell apoptosis and irregular function of the retina [47] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of diabetes, many metabolic changes occur within the cell, leading to an increased level of oxidative stress, which may contribute to the regression of telomere length [45] . There was also an association between DR and increased oxidative stress and activation of proin ammatory signaling pathways [19,46] . As a result of chronic hyperglycemia induces a set of metabolic abnormalities that enhance ROS generation and ultimately lead to oxidative stress in the retina, resulting in retinal cell apoptosis and irregular function of the retina [47] .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of age-related cardiovascular events is in uenced by several aging biomarkers, including telomere length, DNA methylation age, somatic cell mutations, and in ammatory markers [16] . Research progress has indicated that a number of factors contribute to the pathogenesis of DR, including senescence-associated secretory phenotypes, advanced glycation end products, oxidative stress on the endoplasmic reticulum, and impaired autophagy [17][18][19] . CVH is an appropriate prevention and management strategy for reducing the burden of DR due to its close association with established cardiovascular disease (CVD) risk factors.…”
Section: Introductionmentioning
confidence: 99%